Conference Report: The 3rd EBF Focus Meeting: 'Hatching' – emerging technologies approaching the regulated bioanalysis laboratory. (December 2012) - Dijksman, Jessica; Henderson, Neil; Ingelse, Benno; Mulder, Hans; Smeraglia, John; Timmerman, Philip; Brudny-Kloeppel, Margarete; Companjen, Arjen; van Amsterdam, Peter
One hundred and eighty scientists from industry and academia discussed the progress in emerging technologies approaching regulated bioanalysis, with a focus on what potential hurdles prevent them becoming broadly accepted by industry and regulators. The conference delegates agreed that moving innovative technologies forward can only be achieved by providing solid data to support the application. In addition, also establishing an open dialogue with health authorities is key for success. By successfully integrating new technologies in the bioanalytical laboratory we contribute to bringing more safe and efficacious therapies faster to patients.